Systematic Literature Review; Pembelajaran Berdiferensiasi Pelajaran PKn di Sekolah Dasar - Suyadi, Suyadi; Witasari, Rinesti (azkiya, 2024)
Differentiated learning is a learning approach that assumes that each student has different needs, interests, abilities and learning styles. If it is related to PKN subjects, it means that each student has different backgrounds, beliefs and experiences, which can influence the way they understand and apply Pancasila values ​​and citizenship concepts in everyday life. The aim of this research is to analyze the effectiveness of Differentiated Learning in Civics Subjects for Elementary School Students. This research uses the SLR research method or systematic literature review, with the help of the Publish or Perish (POP) tool using the keywords Differentiated education, citizenship education in elementary schools, limited to 2019-2024 or the last 5 years and only 40 articles were then selected based on criteria with a range of citations. Highest and most appropriate to the research theme. 10 articles were produced. The results: Differentiated learning in Civics subjects in elementary schools has proven effective in increasing student understanding and engagement. The results of this research support the importance of applying this method in the context of the Independent Curriculum and show that this approach can provide a more meaningful learning experience for students.